2017
DOI: 10.5194/hess-21-2667-2017
|View full text |Cite
|
Sign up to set email alerts
|

Ross scheme, Newton–Raphson iterative methods and time-stepping strategies for solving the mixed form of Richards' equation

Abstract: Abstract. The solution of the mathematical model for flow in variably saturated porous media described by the Richards equation (RE) is subject to heavy numerical difficulties due to its highly nonlinear properties and remains very challenging. Two different algorithms are used in this work to solve the mixed form of RE: the traditional iterative algorithm and a time-adaptive algorithm consisting of changing the timestep magnitude within the iteration procedure while the nonlinear parameters are computed with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…To compute these processes, CLM uses soil moisture calculated by ParFlow, vegetation characteristics (the type of land use and land cover as well as its physical properties), and the meteorological forcing calculated by WRF. (Homer et al, 2015) and (b) geology (Jennings et al, 1977) and topography (United States Geological Survey, USGS) of the Cosumnes watershed.…”
Section: Numerical-modeling Methodsmentioning
confidence: 99%
“…To compute these processes, CLM uses soil moisture calculated by ParFlow, vegetation characteristics (the type of land use and land cover as well as its physical properties), and the meteorological forcing calculated by WRF. (Homer et al, 2015) and (b) geology (Jennings et al, 1977) and topography (United States Geological Survey, USGS) of the Cosumnes watershed.…”
Section: Numerical-modeling Methodsmentioning
confidence: 99%
“…For example, when θ is taken as the primary variable, the newly updated soil moisture might exceed unity, then the pressure head instead will take the primary role for recalculation. Although improvements were made to minimize such deficiency (Hassane Maina & Ackerer, ; Kees & Miller, ; Krabbenhøft, ), the performance of these techniques tends to be problem specific. Moreover, these methods are restricted to Newton–Raphson iteration schemes.…”
Section: Different Forms Of Rresmentioning
confidence: 99%
“…The saturation degree and the Kirchhoff potential (Ross & Bristow, ) are used as the primary variables for unsaturated and saturated nodes, respectively. Previous research has examined the performance the of Ross method (Crevoisier et al, ; Hassane Maina & Ackerer, ; Varado, Braud, & Ross, ; Varado, Braud, Ross, & Haverkamp, ) with problems involving a wide range of soil constitutive models, initial conditions, and boundary conditions. It is shown that the Ross model is intrinsically mass conservative, and can be computationally less expensive than the conventional iterative methods.…”
Section: Iterative and Noniterative Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why significant efforts have been made in last decades on the development of advanced and appropriate numerical techniques for solving this equation (i.e. Celia et al, 1990;Farthing et al, 2003;Li et al, 2007;Ji et al, 2008;Fahs et al, 2009;Hassane Maina and Ackerer, 2017;Suk and Park, 2019;Ngo-Cong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%